Advanced Drug-Delivery: Systems for Brain Diseases across the Blood-Brain Barrier - Trideva Sastri K.; Kumar H.; Ansari A.J.; Singh A.K.; Khan I. (My University, 2025)
Drug delivery to the brain is crucial for treating brain disorders such as Alzheimer’s disease, Parkinson’s disease, and brain tumours. However, the blood-brain barrier (BBB) poses a significant challenge to drug delivery due to its ability to prevent many drugs from entering the brain. Advanced drug delivery systems have been developed to overcome this challenge by employing different targeting approaches. These advancements offer promising approaches for treating brain disorders by improving the efficiency and specificity of drug delivery across the BBB. This chapter provides an overview of the advanced drug delivery systems to effectively cross the BBB to treat brain disorders. © 2024 selection and editorial matter, Anurag Kumar Singh, Vivek K. Chaturvedi, and Jay Singh; individual chapters, the contributors.